Successive Torsion of the Right Middle and Left Cranial Lung Lobes in a Dog - Breton, Luc (1986)
This case report describes the torsion of two lung lobes in a dog. The animal was first presented for a torsion of the right middle lung lobe. Following the surgical resection of that lobe, the dog suffered another torsion of the left cranial lung lobe (cranial and caudal segments).